Hubungan Beban Kerja dengan Kelelahan Kerja pada Perawat Instalasi Rawat Inap di Rumah Sakit Islam Malahayati Medan - Sumantri, Sakina; Utami, Tri Niswati; Astuty, Delfriana Ayu (LPPM Hang Tuah Pekanbaru, 2024)
Workload arises from the interaction between task demands, the work environment, skills, behavior, and workers' perceptions. It is one of the factors that can lead to fatigue. Nurse work fatigue is a symptom characterized by a decrease in work efficiency, and skills, and an increase in boredom among nurses. This research aims to determine the relationship between workload and work fatigue among nurses working in the Inpatient Unit of Malahayati Islamic Hospital in Medan. The method was a quantitative study using an analytical observational design with a cross-sectional approach. The study involved 71 respondents, who were all nurses working in the inpatient unit at Malahayati Islamic Hospital. The sampling method used was total sampling. The instruments included a workload questionnaire developed by Nursalam, consisting of 13 questions, and a work fatigue questionnaire, which measured feelings of work fatigue with 17 questions. The two variables were analyzed using the Chi-Square test. Results: The study found that 47 respondents (66%) had a heavy workload. Most respondents experienced high levels of work fatigue, with 41 people (58%) falling into the